"Development and validation of classroom interaction instrument for preprimary and primary level of education in Nigeria " (2011)
Classroom Interaction behaviours at the pre-primary level of education especially in Nigeria is still a relatively new concept. Thus, there seem to be no instrument to measure the nature as well as quality of such activities between teachers and learners during instruction. These could be partly the reasons why there is dearth of information on this aspect of preschool activities in Nigeria. The foregoing therefore, underscores the need to develop and validate an instrument (PCIE1) which has the capacity to provide information on typical expected teachers -learner interaction patterns at the pre-primary level of education especially in Nigeria. The instrument was used in three states to observe 36 lessons delivered by 36 teachers in 12 preschool classrooms during instructional delivery in three subject areas (Numeracy, Introduction to letters of the alphabet and Science). 1528 preschoolers were involved in the study. Four research questions were answered using the instrument. Cronbach’s Alpha and Scott's Pie were used to establish the validity and reliability estimate of the instrument (0.85 and .93 respectively). The internal consistency of the items (Cronbach’s Alpha) ranged from .848 to .854 respectively. The classroom interaction behaviours identified include Teacher Prompting Learning Activity, Pupil whole-class Activity, Individual Pupil Activity, Monologue, Teacher not facilitating learning. Confusion. These characteristics were considered very important in producing valid, comparable and generalizable preschool interaction patterns in Nigerian. This is because, the items used are acceptable classroom behaviours which of teachers and learners are expected to exhibit at this level for quality teaching-learning activities to occur